Politics and the Universities in Postrevolutionary Iran - Golkar, Saeid (International Higher Education, 2017)
In the Islamic Republic of Iran, universities are meant to not only produce and distribute knowledge, but also to act as agents of political socialization. Since the establishment of the Islamic regime in 1979, the state has recklessly tried to control and Islamize universities in order to “purify” them from nonconformist students and scholars and train a new generation of devout Muslims for the state bureaucracy. Although these efforts have ultimately failed to create an Islamic university, they have led to massive brain drain and reduced the quality of Iranian higher education.